An?lise de desempenho de t?cnicas de multiplo acesso em redes de r?dios cognitivos com sensoriamento imperfeito - Guimar?es, Pedro Ivo de Almeida (2016)
Cognitive radio is a new paradigm in the development of wireless communication systems that allows dynamic access to the electromagnetic spectrum and is, therefore, a strong candidate as a technological solution to the networks of the future. In these systems, multiple access protocols have a great impact on network performance, being responsible for organizing access to the media of different types of users and avoid or make the interference become tolerable to the primary users. Thesis work analyzes performance in terms of throughput and the average delay of access to cognitive radios network using the Slotted Aloha and Carrier Sense Multiple Access (CSMA) protocol. In the realized study, the previously results presented in the literature, that consider the impact on the performance of the capture effect net and the Packet Error Rate (PER), are extended to also consider the imperfect sensing and different power rating levels in the cognitive network.